Protective Effects of Bifidobacterial Strains Against Toxigenic Clostridium difficile - Wei, Yanxia; Yang, Fan; Wu, Qiong; Gao, Jing; Liu, Wenli; Liu, Chang; Guo, Xiaokui; Suwal, Sharmila; Kou, Yanbo; Zhang, Bo; Wang, Yugang; Zheng, Kuiyang; et al. (Frontiers in Microbiology, 2018)
Probiotics might offer an attractive alternative to prevent and control Clostridium difficile (C. difficile) infection (CDI). Limited information is available on the ability of commercially used bifidobacterial strains to inhibit C. difficile. This study examined the anti-clostridial effects of Bifidobacterium longum JDM301 (JDM301), a widely used commercial probiotic strain in China, in vitro and in vivo. In vitro evaluation revealed a significant reduction in C. difficile counts when JDM301 was co-cultured with C. difficile, which was correlated with the significant decrease in clostridial toxin titres (TcdA and TcdB). Furthermore, the cell-free culture supernatant (CFs) of JDM301 inhibited C. difficile growth and degraded TcdA and TcdB . Notably, the results showed that acid pH promoted the degradation of TcdA by CFs from JDM301. Furthermore, comparative studies among 10 B. longum strains, or 6 species belonging to Bifidobacterium and Lactobacillus or the two genera were performed. Results showed that the inhibitory effect of CFs from JDM301 was similar with the other 8 B. longum strains and higher than strain BLY1. However, when it was neutralized, the significant different was lost. When present together, it was suggested that the acid pH induced by probiotics not only played important roles in the growth inhibition against C. difficile resulting in the reduction of toxins titres, but also directly promoted the degradation of clostridial toxin. JDM301-treated mice showed increased survival rate, less decrease of the body weight, less mucosal damage and down-regualted gut inflammation compared with CD group (infected with C. difficile but without JDM301-treatment). Both the number of C. difficile and toxin levels in cecal contents of JDM301-treated mice was lower than CD group. In summary, our results demonstrated that the commercial strain, JDM301 could be considered a probiotic able to exert anti-toxin capability and most of the CFs from Bifidobacterium were able to inhibit the growth of C. difficile, depending on acid pH. These results highlighted a potential that JDM301 could be helpful in preventing CDI and that most of the bifidobacterial strains could (at least partially) exert protective effects by reducing toxin titres through growth inhibition against toxigenic C. difficile.